Circadian Rhythm Dysfunction Accelerates Disease Progression in a Mouse Model With Amyotrophic Lateral Sclerosis - Huang, Zhilin; Liu, Qiang; Peng, Yu; Dai, Jiaying; Xie, Youna; Chen, Weineng; Long, Simei; Pei, Zhong; Su, Huanxing; Yao, Xiaoli (Frontiers in Neurology, 2018)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease caused by interactions between environmental factors and genetic susceptibility. Circadian rhythm dysfunction (CRD) is a significant contributor to neurodegenerative conditions such as Alzheimer’s disease and Parkinson’s disease. However, whether CRD contributes to the progression of ALS remains little known. We performed behavioral and physiological tests on SOD1G93A ALS model mice with and without artificially induced CRD, and on wild-type controls; we also analyzed spinal cord samples histologically for differences between groups. We found that CRD accelerated the disease onset and progression of ALS in model mice, as demonstrated by aggravated functional deficits and weight loss, as well as increased motor neuron loss, activated gliosis, and nuclear factor κB-mediated inflammation in the spinal cord. We also found an increasing abundance of enteric cyanobacteria in the ALS model mice shortly after disease onset that was further enhanced by CRD. Our study provides initial evidence on the CRD as a risk factor for ALS, and intestinal cyanobacteria may be involved.